উন্নয়ন ভাবনায় : কর্মসংস্থান ও শ্রম বাজার - ইসলাম, রিজওয়ানুল (ঢাকা : দি ইউনিভার্সিটি প্রেস লিমিটেড, 2015)
Study on the unemployment, employment opportunities and labor market in developing countries.
গ্রন্থপঞ্জি ও নিঘন্ট অন্তভূক্ত ।
ESS
HYE Trade International, Donated By Akbar Ali Khan
In Bengali.
Keywords: Unemployment -- Developing countries; Job creation -- Developing countries; Employment stabilization -- Developing countries; Labor market -- Developing countries; Labor supply -- Developing countries; Economics